2018
DOI: 10.3390/su10114310
|View full text |Cite
|
Sign up to set email alerts
|

Soil Quality Change after Reclaiming Subsidence Land with Yellow River Sediments

Abstract: With continuous population growth and decreasing cultivated land area, China’s food security is greatly threatened. Additionally, coal mining in China is primarily underground mining, which causes land subsidence and destroys existing cultivated land. This effect aggravates the contradiction between a growing population and a shrinking area of cultivated land. The purpose of this study was to introduce a method of filling reclamation with Yellow River sediments to restore farmland and realize the sustainable u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…Reclaiming subsidence land with Yellow River sediment appears to be a promising method (Hu, Duo, & Wang, 2018). For mines near the Yellow River, this approach is an important method for restoring cultivated land lost due to coal mining subsidence (Duo & Hu, 2018). F. Shao et al (2013) conducted field infiltration experiments of reclamation farmland soil filled with the Yellow River sediment and found that Yellow River sediment layer did poorly in water retention.…”
Section: Discussionmentioning
confidence: 99%
“…Reclaiming subsidence land with Yellow River sediment appears to be a promising method (Hu, Duo, & Wang, 2018). For mines near the Yellow River, this approach is an important method for restoring cultivated land lost due to coal mining subsidence (Duo & Hu, 2018). F. Shao et al (2013) conducted field infiltration experiments of reclamation farmland soil filled with the Yellow River sediment and found that Yellow River sediment layer did poorly in water retention.…”
Section: Discussionmentioning
confidence: 99%
“…New studies suggest that dredged material-poorly graded sand-from the YRD can be mixed with the saline, clayey flood plain soils to improve agricultural productivity (Mao et al, 2016(Mao et al, , 2018. Additionally, YRD sediments are deposited on agricultural lands adjacent to underground coal mines to combat subsidence and reduce waterlogging (Duo & Hu, 2018).…”
Section: Mitigating Flood Vulnerability-dredge Spoil Repurposing Vs T...mentioning
confidence: 99%
“…In this approach, the subjectivity of assigning weights to evaluation indices is eliminated [19], substantially improving the efficiency of the CLQ evaluation. Many machine learning models are available, but those most frequently used for CLQ evaluation include backpropagation neural network (BPNN) [20,21], decision tree (DT) [22,23], random forest (RF) [18,24], and support vector machine (SVM) [25,26].…”
Section: Introductionmentioning
confidence: 99%